A Case Base Approach for Evaluation of Manufacturing Effectiveness of a Firm Using Analytical Hierarchical Process - Ramesh Ramkisan Lekurwale; D. N. Raut (International Journal of Supply Chain Management, 2014)
High level of Manufacturing Capability (MC) (effectiveness) plays significant role in providing competitive advantage to a firm. However, it is difficult for the firm to evaluate the level of MC, which is given by the consistency of decisions taken in the particular manufacturing environment. For example, in job shop production general purpose facilities and high skilled workforce is essential to obtain the desired level of outputs to satisfy customer expectations. First, Hayes and Wheelwright provided a four stage model for evaluating the level of MC and recently Miltenburg gave a framework that classified these four stages as infant, average, adult and world class. Evaluating MC facilitates the firm to know the present status and also provides a pointer to identify weak decisions for further improvement. This paper presents a case study on evaluating the MC of a firm involved in the production of low volume and high variety products. Job Shop Production System has been used to fulfill these demands. Objective of this research is to find out the current status (level) of MC of a firm based on the consistency of the decisions taken. For this, hierarchical model based on the overall goal as a MC index has been developed by using Analytical Hierarchical Process (AHP) a Multi Criteria Decision Making (MCDM) tool. The MC index of a firm under consideration is computed by evaluating the pattern of decisions taken in the manufacturing which are obtained after discussion with top executives of the company. The results obtained are then compared with ideally required decisions from the same category of manufacturing system (in this case job shop production system). Based on the comparison, status (level) of MC and weak decision areas of the firm have been identified and discussed with the executives.